Evidence for Specific Associations Between Depressive Symptoms, Psychotic Experiences, and Suicidal Ideation in Chilean Adolescents From the General Population - Núñez, Daniel; Monjes, Pía; Campos, Susana; Wigman, Johanna T. W. (Frontiers in Psychiatry, 2021)
Associations between psychotic experiences and suicidal ideation are not yet fully understood, and the potential role of depression in this relationship remains unclear. The current study examined relationships between depressive symptoms, psychotic experiences and suicidal ideation using two complementary approaches on cross-sectional data from a community sample of adolescents aged 13-19 years (N = 1715). First, we investigated the association between the three domains using mediation analysis, showing that depressive symptoms partly mediate the relationship between psychotic experiences and suicidal ideation. Second, we looked at associations between the three domains at item level using network analysis. Specific associations between symptoms of the three domains were found, indicating depressive symptoms of sadness, avolition, pessimism, and selfcriticalness/worthlessness as the most central symptoms in the network. Suicidal ideation was associated with the depressive symptoms pessimism and worthlessness, to social anxiety, and perceptual anomalies. Our results show that the relationship between the mediating effect of depressive symptoms between psychotic experiences and suicidal ideation may be due to specific associations between certain aspects of SI, depression and psychotic experiences. These findings can contribute to the planning of health services and programs aimed at the timely detection of psychopathology and suicidal risk in young people.